Culture change in the UK construction industry: an anthropological perspective - Ian Tellam (Buildings & Cities)
This paper addresses the pressing need for a cultural transformation within the UK construction industry in the wake of the Grenfell Tower fire tragedy in 2017. Through a critique of the Building Safety Act 2022, it argues that while the Act represents a legislative response to the disaster, it may not be sufficient to foster the necessary changes in industry culture. The paper suggests that the Act, and the industry’s response to it, tend to perpetuate existing practices rather than encouraging a radical shift towards safety and responsibility. The paper follows calls advocating for a re-imagined construction culture that prioritises safety, transparency and resident engagement, suggesting that such a shift is essential for preventing future tragedies and restoring public trust in the construction industry. In pursuit of this goal, the paper emphasises the need for systemic, structural and cultural changes that address the complexities of building safety in a holistic manner, urging stakeholders across the sector to commit to meaningful, long-term reform. Practice relevance Cultural change has been identified as a vital aspect to reform of the UK construction industry. Drawing from analyses of the concept of culture and the processes of culture change, the paper argues for a more nuanced and integrated approach to reforming the construction industry. It emphasises the importance of acknowledging and incorporating the lived experiences of residents into the construction process, proposing a model that fosters collaboration across disciplines, involving engineering, social sciences, arts and humanities, to develop a comprehensive understanding of safety that transcends traditional regulatory frameworks. Key to generating change is an acknowledgment that courses of action that only engage existing institutional mechanisms are unlikely to generate radical cultural change, that notions of safety must be built with an inclusive and long-term view throughout the construction process, and that political and power differentials between stakeholders must be addressed to build a genuine and robust relationship of trust.